Analysis of cricoid pressure application: anaesthetic trainee doctors vs. nursing anaesthetic assistants - Yahaya,Nurul Haizam (2016)
ABSTRACT BACKGROUND AND OBJECTIVE: To evaluate the ability of anaesthetic trainee doctors compared to nursing anaesthetic assistants in identifying the cricoid cartilage, applying the appropriate cricoid pressure and producing an adequate laryngeal inlet view. METHODS: Eighty-five participants, 42 anaesthetic trainee doctors and 43 nursing anaesthetic assistants, were asked to complete a set of questionnaires which included the correct amount of force to be applied to the cricoid cartilage. They were then asked to identify the cricoid cartilage and apply the cricoid pressure on an upper airway manikin placed on a weighing scale, and the pressure was recorded. Subsequently they applied cricoid pressure on actual anaesthetized patients following rapid sequence induction. Details regarding the cricoid pressure application and the Cormack-Lehane classification of the laryngeal view were recorded. RESULTS: The anaesthetic trainee doctors were significantly better than the nursing anaesthetic assistants in identifying the cricoid cartilage (95.2% vs. 55.8%, p = 0.001). However, both groups were equally poor in the knowledge about the amount of cricoid pressure force required (11.9% vs. 9.3% respectively) and in the correct application of cricoid pressure (16.7% vs. 20.9% respectively). The three-finger technique was performed by 85.7% of the anaesthetic trainee doctors and 65.1% of the nursing anaesthetic assistants (p = 0.03). There were no significant differences in the Cormack-Lehane view between both groups. CONCLUSION: The anaesthetic trainee doctors were better than the nursing anaesthetic assistants in cricoid cartilage identification but both groups were equally poor in their knowledge and application of cricoid pressure.